ANALISIS IMPLEMENTASI SISTEM INFORMASI AKUNTANSI MENGGUNAKAN SOFTWARE ACCURATE PADA PT RAINBOW TUBULARS MANUFACTURE - Simamora, Ramli Honest; Janrosl, Viola Syukrina E. (SCIENTIA JOURNAL, 2024)
This study analyzes the application of accurate software at PT. Rainbow Tubulars Manufacute especially in the flow of the purchasing cycle, preparation of human resources for the application of accurate software, and fanning reports of receipts of goods into accurate software. This study aims to determine the application of accurate software in the purchase cycle is effective and efficient, and the information generated can help users of accurate information. This research uses qualitative methods and descriptive approaches by describing, describing, collecting data, managing and presenting observational data. The result of this study is that the application of accurate software has been compiled and planned with the existence of standard operating procedures in the purchasing cycle that have been made by the company's management and already have competent human resources in their fields with training for each accurate user to add basic and user proficiency